DETERMINATION OF SYSTEMS THINKING LEADERSHIP AND EDUCATION QUALITY IMPROVEMENT: ANALYSIS OF SPIRITUALITY AND COMMUNITY ENVIRONMENT - Wahyudi AW (Dinasti International Journal of Management Science, 2022)
In this study the authors raised themes related to the factors that influence systems thinking leadership and their impact on improving the quality of education. This study is interesting to discuss in order to see the influence of Spirituality and Community Environment on systems thinking leadership. The research uses library research methods or library research. The results of this study illustrate that systems thinking leadership tends to formulate measurable strategic steps and is able to move all components of the organization. Spirituality is very influential on systems thinking leadership, because it contains the motivation of all good deeds to achieve organizational goals that are worth worship. The community environment is also a crucial factor in systems thinking leadership, because it gives birth to leaders who have experience, ethics and culture within themselves so that the policies taken are a response to community conditions. In the context of education, systems thinking leadership is very influential on the quality of education because it is able to see problems holistically, find solutions, innovate and be able to mobilize resources to improve the quality of education.